Cryo-EM structure of the highly atypical cytoplasmic ribosome of Euglena gracilis - Matzov, Donna (2021)
Ribosomal RNA is the central component of the ribosome, mediating its functional and architectural properties. Here, we report the cryo-EM structure of a highly divergent cytoplasmic ribosome from the single-celled eukaryotic alga Euglena gracilis. The Euglena large ribosomal subunit is distinct in that it contains 14 discrete rRNA fragments that are assembled non-covalently into the canonical ribosome structure. The rRNA is substantially enriched in post-transcriptional modifications that are spread far beyond the catalytic RNA core, contributing to the stabilization of this highly fragmented ribosome species. A unique cluster of five adenosine base methylations is found in an expansion segment adjacent to the protein exit tunnel, such that it is positioned for interaction with the nascent peptide. As well as featuring distinctive rRNA expansion segments, the Euglena ribosome contains four novel ribosomal proteins, localized to the ribosome surface, three of which do not have orthologs in other eukaryotes.